Fitness & Sports Medicine - Wernhart S; Guazzi M; Halle M. (Dynamic Media Sales Verlag, 2020)
Objective: Existing literature has shown heart rate recovery one minute (HRR1) after exercise termination in cardiopulmonary exercise testing (CPET) to correlate with performance, although no data exist on HRR3 and 5 in a population without manifest cardiovascular disease. We aimed to analyze whether HRR3 and 5 correlate with relative oxygen uptake at peak performance (V O2peak) and maximal power (Pmax) as well as with weekly physical activity (PA).Methods: We conducted a sub-analysis of the Euro(pean)Ex(ercise) trial enrolling subjects between 50 and 70 years of age without manifest cardiovascular disease (n=59). Subjects underwent CPET following an individualized ramp protocol with an exercise duration between 10 and 14 minutes. Results: V O2peak (35.69.0 ml/kg/min) and Pmax(245.380.4 W) correlated significantly with HRR1 (22.67.9/min, both p<.001; r=0.50 and 0.48), 3 (44.57.7/min, p=0.018 and 0.010; r=0.33 and 0.35) and 5 (64.814.0/min, p=0.002 and 0.001; r=0.77 and 0.72) in our study population (56.68.2 years). HRR5 correlated more strongly with PA than HRR1 and HRR3 (HRR5: p<0.001; r=0.51; HRR1: p=0.277; r=0.15; HRR3: p=0.156; r=0.20). Subjects with PA>5h/week (8.82.0) differed significantly from those with no regular sports in terms of HRR5 (p<0.010) and V O2peak (p<0.001). Conclusions: HRR5 is a better predictor for maximal exercise capacity than HRR1 or 3.Clinical Relevance: HRR5 should be included in exercise testing.KEY WORDS: Cardiopulmonary Exercise Testing, Heart Rate Recovery, Aerobic Physical Activity